Constructing a feedback loop with circadian clock molecules from the silkmoth, Antheraea pernyi. - Chang, D; Mcwatters, H; Williams, J; Gotter, A; Levine, J; Reppert, S (2003)
Circadian clocks are important regulators of behavior and physiology. The circadian clock of Drosophila depends on an autoinhibitory feedback loop involving dCLOCK, CYCLE (also called dBMAL, for Drosophila brain and muscle ARNT-like protein), dPERIOD, and dTIMELESS. Recent studies suggest that the clock mechanism in other insect species may differ strikingly from that of Drosophila. We cloned Clock, Bmal, and Timeless homologs (apClock, apBmal, and apTimeless) from the silkmoth Antheraea pernyi, from which a Period homolog (apPeriod) has already been cloned. In Schneider 2 (S2) cell culture assays, apCLOCK:apBMAL activates transcription through an E-box enhancer element found in the 5' region of the apPeriod gene. Furthermore, apPERIOD can robustly inhibit apCLOCK: apBMAL-mediated transactivation, and apTIMELESS can augment this inhibition. Thus, a complete feedback loop, resembling that found in Drosophila, can be constructed from silkmoth CLOCK, BMAL, PERIOD, and TIMELESS. Our results suggest that the circadian autoinhibitory feedback loop discovered in Drosophila is likely to be widespread among insects. However, whereas the transactivation domain in Drosophila lies in the C terminus of dCLOCK, in A. pernyi, it lies in the C terminus of apBMAL, which is highly conserved with the C termini of BMALs in other insects (except Drosophila) and in vertebrates. Our analysis sheds light on the molecular function and evolution of clock genes in the animal kingdom.